Sub-faculty of music theory, music history and instrument performing of the Khabarovsk State Institute of Arts and Culture: tendencies and prospects - U. I. Zasukha; S.YU. Lisenko (Высшее образование в России)
The article shows the history of organizing of the Sub-faculty of Music Theory, Music History and Instrument Performing at Khabarovsk State Institute of Arts and Culture. An overview of educational programs and research lines is given as well as problems and prospects of future development of the department according to the cultural situation in our region are outlined.